FORMULASI SEDIAAN GEL ANTISEPTIK TANGAN DAN UJI AKTIVITAS ANTIBAKTERI DARI EKSTRAK ETANOL DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb.) - Eva Sartika Dasopang; Akmal Simutuah (Universitas Medan Area, 2017)
This reseach was conducted to determine the antibacterial activity against Staphylococcus aureus and Eschericia coli from pandanus fragrant ethanol extract formulated in the form of hand gel antiseptic preparations. The ethanol extract was prepared by percolation using 96% ethanol solvent. Phytochemical screening is done on fragrant pandan leaves. Evaluation of hand antiseptic gel preparations included organoleptic testing, homogeneity testing, pH determination, spreading test, stability, irritation testing and antibacterial testing of Staphylococcus aureus and Eschericia coli. The results of phytochemical screening showed that the pandanus fragrant leaves contain alkaloids, tannins, saponins, flavonoids and polyphenols. The pandanus fragrant leaves ethanol extract can be formulated into hand gel antiseptic preparations because the pH is about 6.0-7.1, the spreading power is about 5.06-5.15 cm, stable for 12 weeks and organoleptically a formula with a very 2.5% concentration Favored and does not irritate the skin. The results of antibacterial activity test showed that the preparation with concentration of 10% had the strongest activity with the diameter of 13,23 mm to Staphylococcus aureus and 13,13% to Eschericia coli almost same with dettol stock on the market with diameter 16,43mm to Staphylococcus aureus and 16 , 03% against Eschericia coli.